(3eTGQY CHhGH GdbOS hehGbY CUMGH GdCfSs - (3YdGA GdOhdI GdSefGfjs ((3eMeO GdTQja GdNGfbGgi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi YQafG HYQa PGJg hYQa UaGJg BOGH GdMVQI GdYXei CeG HYO agPg bOSjI eSeGI HeTGQY CHhGH GdbOS heQGJY CUMGH GdCfS eeG jVf Hg Ydi ZjQ Cgdg s
(3BNQgG (B:s
(3dCf Gddg JYGdi TQa GdeDef hGdUGHQ hGdeJbi hGdeMSf HJTTQja GdeYjI GdNGUI ai cJGHg GdYRjR Hbhdg (B( (3Ef Gddg eY GdeDefjf Ef Gddg eY GdUGHQjf Ef Gddg eY GdeJbjf (B) (3hcPdc GdeMSf HdGe GdJCcjO (B( (3Ef Gddg deY GdeMSfjf (B) (3hNUge HGdhdGjI hGdeMHI adeG hUs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs